Experimental Study on the Force Characteristics of Superlong Pile Groups in Silty Sand - Yonghui Li; Dinghao Zhang; Yunlong Liu; Lujie Chen (Advances in Civil Engineering)
Laboratory model testing of single pile and superlong pile groups in saturated silty sand was conducted to investigate the response and bearing behavior of superlong pile groups with a high or low cap under vertical loads. The load transfer mechanism and bearing behavior of the pile shaft were discussed in detail. The load-settlement curve of the loaded superlong pile groups belongs to the type of gradual descent in silty sand. The transferred load decreased along the pile length during loading, but the gradients differed in different positions of the superlong pile group foundation with a high or low cap. The maximum shaft friction of the superlong pile groups with a high and low cap is about 2.5 times and 1.8 times, respectively, than that of the single pile. In addition, the tip resistance of the piles in the pile group foundation is about 2–3.5 times that of the single pile. The friction resistance of the superlong pile group foundation with a low cap was slightly larger than that of the high cap in the entire pile length, and two peaks and one peak, respectively, were observed. Under the ultimate load, the pile-soil maximum relative displacement of the friction on the pile side in the silty sand stratum was about 3% of the pile diameter. Under the ultimate load, the load sharing ratio of the pile side resistance of the two types of pile group foundations was about 60% of the total load. The load sharing ratios at the pile tip of the superlong pile groups with high and low caps are 40% and 33%. Furthermore, equations were proposed to determine the axial capacity of the superlong pile group based on the single pile bearing capacity and were applied to analyze the test pile. The calculated ultimate bearing capacity was similar to the measured value, with a maximum error of only 4.88%, thus validating the proposed method.